DIAMETER BY BASAL AREA RATIO AND COMPETITION ZONES IN Eucalyptus saligna MONOCLONAL STAND - Schneider, Paulo Renato (2011)
The present work was developed in order to study the relation among the diameter and the basal area, the competition zones, the relative density, and the self-tinning in Eucalyptus saligna Smith monoclonal stand, with 238 pair’s data basis of permanent sampling by full density stand distribution, observed from 3 to 18 years old. The results obtained allowed to conclude that Tang’s density model was very precise and efficient. The self-thinning begins when the population reaches an average diameter of 8 cm. The relative density was equal 34.46%, with line gradient of 1.5818 (b). The maximum current annual increment in diameter and between the relative densities was observed between the ages of 14 and 15 years when the relative densities were 12.5% and 25%, characterizing a free growth competition zone among the individuals of the population. The zone of increasing competition between the relative densities of 25 and 50% and the imminent mortality zone occurred between the relative densities of 50 and 100%. The density model allowed detecting five competition zones, in the development of the stands, defined by zones of: excessive space, free growth, increase of competition, complete stock and imminent mortality, in relation to the relative density of the population.